2015
DOI: 10.1007/s13277-015-4007-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CD133+ laryngeal carcinoma cells with chemotherapeutic drugs and siRNA against ABCG2 mediated by thermo/pH-sensitive mesoporous silica nanoparticles

Abstract: Mesoporous silica nanoparticles (MSNs) represent a new form of drug nanocarrier with thermo/pH-coupling sensitivity and site-specificity. CD133(+) Hep-2 laryngeal cancer cells are responsible for multidrug resistance due to elevated expression of ABCG2. Since positively charged nanoparticles could easily uptake nucleic acids, we examined the possibility of using this new drug delivery system to simultaneously deliver different chemotherapeutic drugs and siRNA targeting ABCG2. Our results demonstrated that both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Qi et al targeted laryngeal carcinoma with folic acid-modified MSN. They successfully delivered commonly used chemotherapeutic drugs (paclitaxel, cisplatin, 5-fluoruracil) and siRNA targeting ABCG2, a drug efflux pump involved in multidrug-resistance, to CD133 + positive laryngeal cancer cells in vitro and in vivo [ 46 ]. Before, the group showed a greater reduction in laryngeal tumor size in a mouse model by using cisplatin-loaded and folate-conjugated MSN compared to untargeted MSN [ 19 ].…”
Section: Modifications To Control Cellular Uptake Drug Release Anmentioning
confidence: 99%
“…Qi et al targeted laryngeal carcinoma with folic acid-modified MSN. They successfully delivered commonly used chemotherapeutic drugs (paclitaxel, cisplatin, 5-fluoruracil) and siRNA targeting ABCG2, a drug efflux pump involved in multidrug-resistance, to CD133 + positive laryngeal cancer cells in vitro and in vivo [ 46 ]. Before, the group showed a greater reduction in laryngeal tumor size in a mouse model by using cisplatin-loaded and folate-conjugated MSN compared to untargeted MSN [ 19 ].…”
Section: Modifications To Control Cellular Uptake Drug Release Anmentioning
confidence: 99%
“…[23] Mesoporous silica Cisplatin, 5-fluoroucail, paclitaxel siRNA ABCG2 Downregulation of ABCG2 significantly enhanced the drug-induced apoptosis and inhibited Hep-2 (laryngeal) tumour growth in vivo. [24] PLGA Paclitaxel Wedelolactone SOX-2, ABCG2…”
Section: Curcuminmentioning
confidence: 99%
“…For example, Qi et al (2015) loaded NPs with siRNA targeting ABCG2 and a chemotherapeutic (cisplatin, 5-fluoroucail or paclitaxel) for the treatment of CD133+ laryngeal carcinoma. The authors reported that the downregulation of ABCG2 significantly enhanced chemotherapeutic drug-induced apoptosis, leading to superior control of tumour growth [24]. Similarly, co-delivery of wedelolatone (Wdl) and paclitaxel incorporated within PLGA NPs downregulated the ABCG2 and SOX-2 expression, sensitising tumour cells to paclitaxel treatment, and reducing the overall percentage of ALDH+ CSCs in vitro and in solid tumours [25].…”
Section: Nanotherapeutic Approaches To Target Cancer Stem Cellsmentioning
confidence: 99%
“…But many papers have reported targeting CD133 + cells therapy for other cancers. More recently, Qi et al (2016) loaded chemotherapeutic antitumor drugs and small interfering RNA (siRNA) against CD133 + into mesoporous silica nanoparticles (MSNPs) with thermo/pH-coupling sensitivity and site-specificity. These MSNPs successfully inhibited its growth in vivo in a laryngeal cancer mouse model by eliminating CD133 + cells (Qi et al, 2016).…”
Section: Stem Cell Surface Markers In Renal Cscsmentioning
confidence: 99%